An empirical study on the impact of organizational justice on employee job satisfaction: Evidence from the Manaseer industrial complex in the mining sector - Madadha, Hareth; Al-Ma’aitah, Noor (Journal of Asian Scientific Research, 2025)
Employee job satisfaction is a key dependent variable in organizational behavior research as it is associated with job performance, retention, and workplace culture. It is widely accepted that employees who are satisfied with their job experience are more productive and likely to be retained by an organization. Organizational justice (i.e., distributive justice, procedural justice, and interactional justice) is linked to job satisfaction, as perceived fairness is integral to job satisfaction, working life, and employee engagement. However, there is minimal research concerning employee job satisfaction relative to organizational justice in the industrial and mining sectors of Jordan. This study aimed to determine whether organizational justice impacts employee job satisfaction within the Manaseer Industrial Complex in Jordan. A quantitative, cross-sectional study was conducted utilizing a structured questionnaire delivered to 247 employees in a variety of job levels. Data was analyzed using reliability tests, correlation, and multi-model regression analyses. Results showed a statistically significant positive relationship for distributive and interactional justice on job satisfaction, whereas procedural justice did not demonstrate a significant relationship on job satisfaction. In conclusion, organizations within the mining sector should consider the value of a transparent reward system to advance job satisfaction for employees and to develop an organizational culture that supports the well-being of employees.